(11)

where ${\mathbf{S}}_{i}$ is the encoder state after the encoding of bit ${d}_{i}$.

The LLR of bit ${d}_{i}$ can then be expressed as

$\mathrm{\Lambda}({d}_{i})=\mathrm{ln}\frac{{\mathrm{\Sigma}}_{m}{\lambda}_{i}^{1}(m)}{{\mathrm{\Sigma}}_{m}{\lambda}_{i}^{0}(m)}\text{.}$ (12)

(12)

For the code of Figure 26, $\mathrm{\Lambda}({d}_{i})$ is written as

$\mathrm{\Lambda}({d}_{i})=\frac{{\lambda}_{i}^{1}(0)+{\lambda}_{i}^{1}(1)+{\lambda}_{i}^{1}(2)+{\lambda}_{i}^{1}(3)}{{\lambda}_{i}^{0}(0)+{\lambda}_{i}^{0}(1)+{\lambda}_{i}^{0}(}$

Start Free Trial

No credit card required